Detoxification technology and mechanism of processing with Angelicae sinensis radix in reducing the hepatotoxicity induced by rhizoma Dioscoreae bulbiferae in vivo - Song, Lingling; Wang, Junming; Gong, Mingzhu; Zhang, Yueyue; Li, Yamin; Wu, Xiaohui; Qin, Lingyu; Duan, Yaqian (Frontiers in Pharmacology, 2022)
Rhizoma Dioscoreae Bulbiferae (RDB) was effective on relieving cough and expectorant but accompanied by severe toxicity, especially in hepatotoxicity. A previous study found that processing with Angelicae Sinensis Radix (ASR) reduced RDB-induced hepatotoxicity. However, up to now, the optimized processing process of ASR-processed RDB has not been explored or optimized, and the detoxification mechanism is still unknown. This study evaluated the detoxification technology and possible mechanism of processing with ASR on RDB-induced hepatotoxicity. The optimized processing process of ASR-processed RDB was optimized by the content of diosbulbin B (DB), the levels of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and histopathological analysis. The processing detoxification mechanism was evaluated by detecting the antioxidant levels of nuclear factor E2 related factor 2 (Nrf2) and its downstream heme oxygenase 1 (HO-1), quinone oxidoreductase 1 (NQO1), glutamylcysteine ligase catalytic subunit (GCLM), and the levels of downstream antioxidant factors of Nrf2. Besides, the antitussive and expectorant efficacy of RDB was also investigated. This work found that processing with ASR attenuated RDB-induced hepatotoxicity, which can be verified by reducing the levels of ALT, AST and ALP, and reversing the pathological changes of liver histomorphology. And the optimized processing process of ASR-processed RDB is "processing at a mass ratio of 100:20 (RDB:ASR) and a temperature of 140℃ for 10 min". Further results corroborated that the intervention of processed products of ASR-processed RDB remarkably up-regulated the Nrf2/HO-1/NQO1/GCLM protein expression levels in liver, and conserved antitussive and expectorant efficacy of RDB. The above findings comprehensively indicated that the optimized processing process of ASR-processed RDB was "processing at a mass ratio of 100:20 (RDB:ASR) and a temperature of 140℃ for 10 min", and the processing detoxification mechanism involved enhancing the level of Nrf2-mediated antioxidant defense in liver as a key target organ.